The effect of depth on the drag force during underwater gliding: a cfd approach - Machado, L.; Ribeiro, J.; Costa, L.; Silva, A.; Rouboa, A.; Mantripragada, N.; Marinho, D.; Fernandes, R.; Paulo, J. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
Swimming events are the sum of a gliding part and a swimming part. The gliding is used after the start and turns, and this phase typically corresponds to 10-25% of the total event time (Chatard et al., 1990). Taking this into account, one can notice that gliding is very important in swimming events and, therefore, its biomechanical study in order to make it more efficient is also very relevant. The gliding can be studied experimentally, by using voluntary subjects gliding in a controlled manner in a swimming pool (using video or velocimetry, for instance), or by using Computational Fluid Dynamics (CFD). Although the experimental method gives "real" values it also presents some drawbacks, like usually imposing a heavy setup and also the fact that it is difficult to control all variables, like depth, attitude or intersegment positions of the swimmer. The CFD method does not have these limitations and its results are comparable to those obtained by the experimental method (Bixler & Riewald, 2002; Silva et al., 2005; Bixler et al., 2007; Vilas Boas et al., 2010). This work aims to study the effects of the depth and velocity on the drag force experienced by a swimmer during gliding using the CFD method.